Mechanics Analysis and Research of Multi- metal Belt in Automotive Continuously Variable Transmission - Wang Yunxia; Qi Xiaomin (Jixie chuandong)
The continuously variable transmission can significantly improve the dynamic performance of automotive,which is the development direction of automobile transmission. The metal belt is the main transmission component of automotive continuously variable transmission,the four layers metal band analysis model is established,and the force and change of velocity of each layer of metal belt in different working conditions are analyzed. The results show that when the metal belt between the friction rate is small,the major tension used for transmission torque is in the first layer of metal band,with the friction rate between each layer of metal band belt increase,the four layers of metal band relative slip decreases and the velocity difference becomes small.The friction between metal bands belt can be effective delivery of torsional moment,the final metal belt tension began to evenly distribute to the four layers of metal belt. With the metal bands belt outward,the operating speed of band gradually decreases on the driver pulley,through the mechanical analysis of automotive continuously variable transmission,which provides an important reference for the design and dynamic characteristics study.